Pengaruh Konsentrasi Larutan Pupuk Boron Juragan Terhadap Pertumbuhan Bibit Kopi Robusta (Coffea robusta L.) - Yanto Yanto; Irmawati Irmawati; Ansyori Ansyori; Bambang Purwanto (JURNAL WACANA PERTANIAN, 2023)
Boron is one of the most important micronutrients for plants. Boron plays a role in the formation or reproduction of cells, especially in the point of shoot growth, as well as in the growth of pollen, flowers and roots. The aim of the research was to determine the effect of the concentration of Juragan Boron fertilizer solution on the growth of Robusta coffee (Coffea robusta L.) seedlings. The study used a randomized block design (RBD) with 5 replications and the treatment was the concentration of boron fertilizer which consisted of 5 levels, namely B0 = without boron fertilizer (control), B1 = 1 g.l-1 water, B2 = 2 g.l-1 water, B3 = 3 g.l-1 water, B4 = 4 g.l-1 water. The data was tested using Orthogonal Polynomial Test. The conclusion of the study is that the optimal concentration of Juragan Boron fertilizer solution is between 1.34--2.08 g.l-1 of water with a contribution of between 44.18--86.87% in influencing the growth of Robusta coffee seedlings.